Interactions among Trypanosoma brucei RAD51 paralogues in DNA repair and antigenic variation - Dobson, Rachel (Blackwell Publishing Ltd, 2011)
Homologous recombination in Trypanosoma brucei is used for moving variant surface glycoprotein (VSG) genes into expression sites during immune evasion by antigenic variation. A major route for such VSG switching is gene conversion reactions in which RAD51, a universally conserved recombinase, catalyses homology-directed strand exchange. In any eukaryote, RAD51-directed strand exchange in vivo is mediated by further factors, including RAD51-related proteins termed Rad51 paralogues. These appear to be ubiquitously conserved, although their detailed roles in recombination remain unclear. In T. brucei, four putative RAD51 paralogue genes have been identified by sequence homology. Here we show that all four RAD51 paralogues act in DNA repair, recombination and RAD51 subnuclear dynamics, though not equivalently, while mutation of only one RAD51 paralogue gene significantly impedes VSG switching. We also show that the T. brucei RAD51 paralogues interact, and that the complexes they form may explain the distinct phenotypes of the mutants as well as observed expression interdependency. Finally, we document the Rad51 paralogues that are encoded by a wide range of protists, demonstrating that the Rad51 paralogue repertoire in T. brucei is unusually large among microbial eukaryotes and that one member of the protein family corresponds with a key, conserved eukaryotic Rad51 paralogue.